2021
DOI: 10.1038/s41598-021-90894-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sPLA2IIA performance with high-sensitive CRP neutrophil percentage PCT and lactate to identify bacterial infection

Abstract: Early bacterial infection (BI) identification in resource-limiting Emergency Departments (ED) is challenging, especially in low- and middle-income counties (LMIC). Misdiagnosis predisposes to antibiotic overuse and propagates antimicrobial resistance. This study evaluates new emerging biomarkers, secretory phospholipase A2 group IIA (sPLA2-IIA) and compares with other biomarkers on their performance characteristic of BI detection in Malaysia, an LMIC. A prospective cohort study was conducted involving 151 cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
2
5
0
1
Order By: Relevance
“…The mean age of the sepsis patients in our study was 55.60±17.20 years, and there were more males (57.63%) than females (42.37%) in this group. This finding is in agreement with studies by Tan et al, Deme et al, and Anglès et al as well as other previous studies, as they also found similar mean ages between the groups and a male preponderance [2,[14][15][16][17]. Another study by Tan et al, also documented a similar mean age, although the distribution of males and females was equal in their study [18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The mean age of the sepsis patients in our study was 55.60±17.20 years, and there were more males (57.63%) than females (42.37%) in this group. This finding is in agreement with studies by Tan et al, Deme et al, and Anglès et al as well as other previous studies, as they also found similar mean ages between the groups and a male preponderance [2,[14][15][16][17]. Another study by Tan et al, also documented a similar mean age, although the distribution of males and females was equal in their study [18].…”
Section: Discussionsupporting
confidence: 92%
“…The current study observed significantly higher mean PCT and PLA2 in sepsis patients when compared to the non-sepsis group. This was supported by Tan et al and Anglès et al who also found these biomarkers to be elevated in sepsis patients [14,16]. Tambo et al and Varela-Patiño et al also found a strong association between PCT and sepsis [19,20].…”
Section: Discussionmentioning
confidence: 73%
“…Не было установлено корреляций между sPLA2 и уровнями CRP, D-димера и количеством лейкоцитов [39]. Вместе с тем установлены положительные корреляции уровня sPLA2-IIA с показателями NEWS2, уровнем глюкозы и отрицательные с креатинином мочевины, скоростью клубочковой фильтрации, гематокритом, сатурацией гемоглобина, что также подтверждает зависимость sPLA2-IIA от тяжести COVID-19 инфекции [103,104].…”
Section: коронавирус Sars-cov-2unclassified
“…The first clinical study to determine serum PLA 2 activity, subsequently shown to be hGIIA activity, in any disease established an association between this activity and severity of disease in sepsis and septic shock [ 18 ]. This relationship is robust with hGIIA being recognized as a key biomarker and predictor of mortality in this disease [ 105 , 106 ]. In addition, a single study establishes that hGIIA is also an important marker in combination with procalcitonin in predictively distinguishing patients with sepsis from patients with noninfectious systemic inflammatory response syndrome on presentation at Emergency Departments (ED) [ 107 ].…”
Section: Hgiia Functionmentioning
confidence: 99%